ADAMTS4, 5, 9, and 15 Expressions in the Autopsied Brain of Patients with Alzheimer's Disease: A Preliminary Immunohistochemistry Study. Issue 1 (1st March 2016) - Pehlivan, Sultan; Fedakar, Recep; Eren, Bulent; Akyol, Sumeyya; Eren, Filiz; Inanir, Nursel Turkmen; Gurses, Murat Serdar; Ural, Mustafa Numan; Tagil, Suleyman Murat; Demircan, Kadir
ABSTRACT: Objective : Recent studies performed in the central nervous system highlight the pathophysiological relevance of A disintegrin-like and metalloproteinase with thrombospondin motifs (ADAMTS) genes and their protein products. The determination of alterations in expression profiles of ADAMTS family genes in Alzheimer's disease (AD) patients may contribute to the explanation of tissue pathology and also new ideas for remedial approaches for this incurable but preventable disease. Therefore, the goal of this study was to describe and identify the distribution, characteristics, and any changes in the expression, in other words, immunoreactivity, for aggrecanases (ADAMTS4, 5, 9, and 15) proteins in AD brain. Methods : Nine cases that were autopsied in the Council of Forensic Medicine, Bursa Morgue Department in 2013, were selected. All of the cases were sent for autopsy to the institution within 8 hours after death. At autopsy, tissue samples were obtained for histopathological examination of organs for determining the cause of death. Out of these, two cases were diagnosed with AD by neurologists when they were alive. Immunohistochemical staining was performed on the brain slides by using relevant primary and secondary antibodies against aggrecanase proteins. All images were acquired using a X200 objective of a microscope (Olympus BX53) and evaluated by the staining intensity using a semi-quantitative scoring system. Results : ADAMTS4 and 5 were slightly under-expressed in the brains from autopsied AD cases compared to those of control brains and suggested that extracellular matrix (ECM) degradation was not endorsed in AD brain. On the other hand, ADAMTS9 and 15 aggrecanases were not found to be expressed in correspondent brain sections of AD and control cases. Conclusion : The current study demonstrated that some aggrecanases were found to be under-expressed in AD brains. Additional studies in which all ADAMTS enzymes will be studied in terms of mRNA and protein levels are needed to understand the relative contributions of ADAMTS genes and proteins in AD brains.